Clinical and cardiopulmonary effects of atropine-diazepam-ketamine with and without guaifenesin in calves suffering from acute renal failure - Sarma, B; Kumar, Amresh (The Indian Journal of Animal Sciences, 2012)
Acute renal failure was produced by injecting uranyl nitrate @ 5 mg/kg body weight in 16 crossbred Jersey calves. Atropine sulphate @ 0.04 mg/kg i m - diazepam @ 0.5 mg/kg i v - ketamine @ 5 mg/kg i v; or atropine @ 0.04 mg/kg i m - diazepam @ 0.05 mg/kg I v - (guaifenesin 5% + thiopentone 0.2%) @ 1.5 mg/kg - ketamine @ 5 mg/kg j v were given in 8 animals each respectively. A good anaesthesia with better muscle relaxation was produced in animals given atropine-diazepam (guaifenesin + thiopentone) - ketamine. Significant (P